The effect of two different intensities of resistance training with blood flow restriction on muscle strength, body fat percentage and serum level of Irisin in overweight women - Mahshid Mohammadiyan; Mahdi Ghahremani Moghaddam; Elham Hakkakdokht (Mashhad University of Medical Sciences, 2021)
Introduction: The prevalence of overweight and obesity and its complications are rapidly increasing in the world. Therefore, new ways are needed to prevent and cure this health dilemma. This study was performed with aim to compare the effect of six weeks of resistance training along with blood flow restriction (Kaatsu) with two different intensities on body fat percentage, muscle strength, and serum level of Irisin in overweight women. Methods: This semi-experimental study was performed in 2019 on 42 overweight women in Mashhad. The subjects were randomly assigned into three groups: resistance exercises with blood flow restriction (BFR) and intensity of 20-30% of 1repetition maximum (1RM), resistance training with BFR and intensity of 40-50% and control group. The training groups received training three sessions per week and 60-50 minutes each session for six weeks. Before and after the intervention, serum levels of Irisin, muscle strength and fat percentage were taken. Data were analyzed by SPSS software (version 23) and ANCOVA test. p < 0.05 was considered statistically significant. Results: Six weeks of resistance training along with Kaatsu with two variable intensities resulted in a significant increase in strength in the post-test (P=0.001). Changes in irisin levels and fat percentage were not significantly different between the two groups (P≤0.05). Conclusion: Resistance training along with Kaatsu significantly decreased fat percentage at 20-30% of intensity without changes in serum level of irisin.